Memória organizacional, memória dos músicos e reprodutibilidade técnica no projeto Unimúsica da UFRGS - Viana Filho, Rubens Clair (2017)
The present dissertation revolves around the “Unimúsica Project”, allocated within the Pro-Rectory of Extension of the Federal University of Rio Grande do Sul (UFRGS). The Unimúsica Project began in 1981 and remains active to this date. This dissertation comprises the period from 1981 to 2016, and aims to study such project under the perspectives of organizational memory, technical reproducibility and memory of the musicians in the vision of Halbwachs, as well as to present a memorial album on the project. The text is thus divided into three parts: after the introduction, the second part contains three articles that have analyzed the aforementioned project through different perspectives. Finally, the third presents the structure of the memorial album that serves as a technical product. Next, considerations related to the article's’ main findings and final product are drawn: (1) a gap has been identified in terms of meaningful records related to the Unimúsica Project’s organizational memory. These may have effects on organizational learning and decision-making, causing workers to work by projects and rely on “do-ityourself” practices amidst a Bureaucratic context, whereas there is evidence of a loyal public (some 8500 spectators per year); (2) when it comes to technical reproducibility, one can identify the existence of a "here and now related to the work of art" at the beginning of the Unimúsica Project, though technology and its digital reproducibility currently do not allow people to more closely see art with distinctions of values. Still, it does not detract from the importance of the original values of the work of art, as pointed out by Benjamin (1955) - in fact technology adds up to it under several aspects; (3) some photographic records of gigs hosted by the Unimúsica Project have been analysed in terms of musicians’ collective memory. It is suggested that the artist and their score can be considered as a whole, which explores their own emotiveness and sensitivity, resulting in music interpreted their own way in the “here and now” logic, seen as an "invisible demon" the musicians can trap and dominate, made clear in the audience’s emotions; and (4) the Master degree’s technical project entitled "Memorial Album of the UFRGS’ Unimúsica Project (1981-2016)", through which it has been found that there were 261 musical events named gigs, 11 recitals, 13 shows, 3 concerts and 2 festivals, amounting to 291 presentations in its 35 years of existence (1981-2016).